An update on the genetics of pheochromocytoma - Karasek, D; Shah, U; Frysak, Z; Stratakis, C; Pacak, K (Journal of human hypertension, 2013)
Pheochromocytomas (PHEOs) and paragangliomas (PGLs) are rare neuroendocrine tumors. About 30% or more of them are thought to be of inherited origin due to germ-line mutations in at least 10 well-characterized genes. There are data linking specific genotypes of these tumors to specific locations, typical biochemical phenotypes or future clinical behaviors. Conversely, clinical features, catecholamine production and immunohistochemistry evaluation can help with the proper order of genetic testing for PHEO and PGL. The identification of a germ-line mutation can lead to an early diagnosis, appropriate treatment, regular surveillance and better prognosis not only for the patient but also for their family members. Moreover, the latest discoveries in molecular pathogenesis of these tumors will provide an important basis for future personalized therapy.
Keywords: Genetic Predisposition to Disease; nádory nadledvin; genetické testování; dědičnost; Prognosis; Predictive Value of Tests; feochromocytom; prediktivní hodnota testů; Paraganglioma, Extra-Adrenal; Patient Selection; fenotyp; výběr pacientů; individualizovaná medicína; Phenotype; prognóza; Humans; Catecholamines; nechromafinní paragangliom; Heredity; Pheochromocytoma; Adrenal Gland Neoplasms; Precision Medicine; genetická predispozice k nemoci; Genetic Testing; katecholaminy; lidé